LITERATUR REVIEW: HUBUNGAN KINERJA LINGKUNGAN DAN PROFITABILITAS TERHADAP PENGUNGKAPAN LINGKUNGAN PERUSAHAAN DI INDONESIA - Dwita Diajeng Syawaliah (LPPM Universitas Putera Batam, 2026)
The growing concern over environmental issues has encouraged companies to enhance transparency through environmental disclosure practices. This study aims to examine empirical findings from previous research regarding the relationship between environmental performance and profitability on corporate environmental disclosure in Indonesia. The method used is a literature review by analyzing 15 relevant journal articles published within the last five years. The results indicate that environmental performance generally has a positive effect on environmental disclosure. Companies with superior environmental management tend to be more open in presenting environmental information as an effort to enhance legitimacy in the eyes of the public. Meanwhile, the influence of profitability on environmental disclosure shows varying results, some studies find a positive relationship, others a negative one, and some report no significant effect. This study is expected to contribute to expanding research in the field of environmental accounting and serve as a reference for future researchers to develop more comprehensive studies on the determinants of environmental disclosure in Indonesia. Keywords: Environmental Performance, Profitability, Environmental Disclosure